Anyone but you - Hauck, Rachel, 1960-; Padgett, Carrie (Hauck, Rachel, 1960- Hearts Bend, 2026)
She thought she'd left her small-town past behind-until love brought her home. Chloe LaRue doesn't do second chances. As a celebrated pastry chef in Paris, she built a beautiful life with her adventurous husband Jean-Marc -- until a tragic skiing accident shattered everything. Only ten months after losing the love of her life, she's forced to return to sleepy Hearts Bend, Tennessee, to care for her cancer-stricken mother. But some people are worth coming home for. Enter Sam Hardy -- the NFL superstar quarterback who crushed her teenage dreams and is now her boss at Haven's Bakery. Once the golden boy who broke her fifteen-year-old heart, he's fighting his own demons: a playboy reputation he's desperate to shed and a bitter feud with his father that's poisoned his soul. When Chloe walks back into his life -- still beautiful, still wounded, still the only woman who ever saw the real him -- everything changes. -- Provided by publisher.